AKTIVITAS ANTIOKSIDAN TOTAL FLAVONOID DAN FENOL KULIT BATANG GAYAM (Inocarpus fagiferus Fosb) - Santi, Sri Rahayu; Sukadana, I Made (Jurnal Kimia (Journal of Chemistry); Vol. 9, No. 2 Juli 2015DO - 10.24843/JCHEM.2015.v09.i02.p04, 2015)
These researchs aim to know of contain total flavonoid, total phenol and antioxidant activity in vitro of gayam stem bark of each extract (Inocarpus fagiferus Fosb). The result of extraction 1 kg stem bark of gayam with 8500 mL ethanol (5 x 1700 mL) to yield 30 g of concentrated extract its brown red. The partition of 15 g concentrated ethanol extract with chloroform, n-buthanol, and water to yields of 1.5g yellowish concentrated chloroform extract,  5.87 g brown red concentrated n-buthanol extract and 5.63 g concentrated water extract respectively. The result of phytochemical test of fourth extract shown that the ethanol, n-buthanol, and water extracts qualitatively contain of flavonoid and phenol compounds, while the chloroform extract only to contain phenol compound with much total flavonoid in ethanol extract 0.14 % and less at n-buthanol extract is 0.09 %. The result of antioxidant activity with DPPH method shown that water and  n-buthanol extract of gayam stem bark have value IC 50 was 20 ppm smaller than  IC 50 of vitamin E was 25 ppm its mean the water and  n-buthanol extract of gayam stem bark have the highest potent scavenger of free radical. The result of antioxidant activity with lipid peroxide-ammonium thiocyanate method shown the extract n-buthanol extract have the highest potent  inhibition of formed lipid peroxide (63.04%), it is higher than antioxidant activity of vitamin E (50.39%).
Keywords: Inocarpus fagiferus Fosb, flavonoid, phenol, antioxidant